2018
DOI: 10.5271/sjweh.3701
|View full text |Cite
|
Sign up to set email alerts
|

Identifying return-to-work trajectories using sequence analysis in a cohort of workers with work-related musculoskeletal disorders

Abstract: Using population-based data in British Columbia over one year, we constructed nine return-to-work trajectory clusters after a work-related musculoskeletal injury. Workers with back strains were most likely to have early sustained return-to-work trajectories, workers with fractures or dislocations were more likely to have sickness absence trajectories or non-return-to-work trajectories. The results can guide approaches and interventions to improve return-to-work outcomes.Affiliation:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 24 publications
2
33
1
Order By: Relevance
“…Using sequence and cluster analysis provided a more comprehensive picture of various SA and DP patterns among injured bicyclist. This can be seen as a good complement to traditional regression analysis [30][31][32]43]. The advantage of methods allowing for complex pattern analysis is illustrated in the present study especially by the clusters "Episodic SA" and "Long-term SA", where the heterogeneity of SA and DP can be seen.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Using sequence and cluster analysis provided a more comprehensive picture of various SA and DP patterns among injured bicyclist. This can be seen as a good complement to traditional regression analysis [30][31][32]43]. The advantage of methods allowing for complex pattern analysis is illustrated in the present study especially by the clusters "Episodic SA" and "Long-term SA", where the heterogeneity of SA and DP can be seen.…”
Section: Discussionmentioning
confidence: 69%
“…Sequence analysis could be a suitable method to also gain knowledge on different patterns over time regarding, e.g., individuals' timing, duration, and order of different types of events, such as SA and DP [29] and the interest for such analyses has increased lately. Sequence analysis has been used in several studies, with the observation that the identified heterogeneity between the sequences can be a good complement and adds additional value to traditional regression analyses [30][31][32]. Thus, to get a more complete picture of the long-term patterns regarding SA and DP in relation to a bicycle crash there is a need for studies using more comprehensive methods.…”
Section: Introductionmentioning
confidence: 99%
“…Statistics Norway provided detailed administrative register data [16] on income, employment, welfare benefits (FD-Trygd), education (the Norwegian National Education Database), and demographics (the Central Population register). In previous studies of RTW using sequence analysis, register data has been linked to subsamples based on intervention [3, 9, 10] or region [11] with follow-up times of a few years. Here, individual’s labour-market participation was followed from 2004Q1 to 2013Q4 (excluding those who are self-employed).…”
Section: Methodsmentioning
confidence: 99%
“…Here, individual’s labour-market participation was followed from 2004Q1 to 2013Q4 (excluding those who are self-employed). A quarterly time-scale was used to facilitate the classification of trajectories, which can be complicated by long sequences [11, 17]. Individuals who died during the study period ( n = 198) or who had missing baseline socio-demographic characteristics ( n = 1421) were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we showed the importance of measuring RTW as a trajectory, and thereby including modified RTW as one of the events in the sickness absence trajectory to explain time to RTW [ 34 ]. In this study we were able to show that MJHs in most cases take longer to RTW compared to SJHs, but future studies would benefit from addressing the issue of more refined or detailed measures of RTW, as well as the description of MJHs.…”
Section: Discussionmentioning
confidence: 99%